2022
DOI: 10.3390/horticulturae8060557
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Volatile Organic Compounds from Bacillus velezensis CE 100 against Colletotrichum gloeosporioides

Abstract: Colletotrichum gloeosporioides is the most prevalent phytopathogen, causing anthracnose disease that severely affects the production of various fruit trees, including walnut and jujube. In this study, the volatile organic compounds (VOCs) from Bacillus velezensis CE 100 disrupted the cell membrane integrity of C. gloeosporioides and reduced the spore germination by 36.4% and mycelial growth by 20.0% at a bacterial broth concentration of 10%, while the control group showed no antifungal effect. Based on the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…In the present study, inhibition of A. alternata and S. rolfsii growth by mVOCs emitted by both bacterial strains was observed under control conditions (0 mM NaCl). In agreement with our results, it has been shown that some mVOCs produce the inhibition of the vital activity of fungi in the soil, thereby negatively affecting the germination and growth of fungi [ 73 , 74 ]. Ossowicki et al [ 75 ] also showed this effect, when two fungal strains Rhizoctonia solani AG2.2IIIB and Fusarium culmorum PV were used against the Pseudomonas donghuensis strain P482, with the same being reported for the P. fluorescens ZX strain against Penicillium italicum [ 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, inhibition of A. alternata and S. rolfsii growth by mVOCs emitted by both bacterial strains was observed under control conditions (0 mM NaCl). In agreement with our results, it has been shown that some mVOCs produce the inhibition of the vital activity of fungi in the soil, thereby negatively affecting the germination and growth of fungi [ 73 , 74 ]. Ossowicki et al [ 75 ] also showed this effect, when two fungal strains Rhizoctonia solani AG2.2IIIB and Fusarium culmorum PV were used against the Pseudomonas donghuensis strain P482, with the same being reported for the P. fluorescens ZX strain against Penicillium italicum [ 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…Twisted hyphae were also observed in Colletotrichum acutatum, Colletotrichum coccodes, Colletotrichum dematium, and Colletotrichum gloeosporioides after treatment with the VOC mixture produced by B. velezensis CE 100 [ 74 ]. VOCs of B. velezensis JRX-YG39 have caused hyphae abnormalities such as coiling and discoloration in Colletotrichum gloeosporioides (walnut and jujube anthracnose), while the pure compounds 5-nonylamine and 3-methylbutanoic acid have caused similar morphological changes followed by cell wall lysis and fracturing [ 75 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…A significant decrease in spore density of Fusarium verticillioides and Fusarium graminearum was observed after treatment with B. mojavensis I4 VOCs [ 76 ]. The different concentrations of 1%, 3%, 5%, 7%, and 10% of the VOCs produced by B. velezensis CE 100 reduced the spore germination of Colletotrichum gloeosporioides (walnut and jujube antrachnose) by 15.4%, 18.9%, 25.4%, 30.0%, and 36.4%, respectively, with remarkably reduced germ tube elongation [ 75 ]. Incompact and irregular structures of spores of Verticillium dahliae , causing cotton Verticilium wilt, together with visible holes on the spores’ surface, appeared after treatment using styrene produced by Bacillus sp.…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…While they are not considered to be phytohormones per se, the volatile organic compounds (VOCs) that are synthesized by a wide range of soil bacteria have recently been shown to play a significant role in plant growth promotion [ 6 , 31 , 32 , 33 , 34 ]. The growth promotion effect of VOCs is largely attributed to the modulation of the synthesis and/or metabolism of known phytohormones, synthesized by either PGPB or by plants [ 35 , 36 ]. The bacterial synthesis of VOCs has been shown to increase plant photosynthesis, and the content of gibberellin, auxin, and cytokinin, depending upon the plant and the particular organic compounds involved.…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%